1989
DOI: 10.1088/0029-5515/29/8/012
|View full text |Cite
|
Sign up to set email alerts
|

The highest energy confinement measured on TMX-U

Abstract: The highest confinement parameters measured on the Tandem Mirror Experiment-Upgrade (TMX-U) at Lawrence Livermore National Laboratory are summarized. The highest TMX-U global energy confinement product was 2 × 10l0 cm−3·s and the highest central cell electron temperature was 0.28 keV. Both were achieved during standard tandem mirror operation with a central cell density of 6 × 1012 cm−3. During thermal barrier operation, strong end plugging was limited to densities below 3 × 10l2 cm−3 and the maximum global en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…The exception was the TMX-U experiment at Lawrence Livermore National Laboratory where electron temperatures up to 0.28 keV were obtained with ECR heating (ECRH), but these studies were terminated soon after that 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exception was the TMX-U experiment at Lawrence Livermore National Laboratory where electron temperatures up to 0.28 keV were obtained with ECR heating (ECRH), but these studies were terminated soon after that 6 .…”
Section: Introductionmentioning
confidence: 99%
“…However, for many years the use of this method in open magnetic configurations has been limited either to plasma heating in relatively compact laboratory installations 1 , or to MHD stabilization and generation of fast electron population in a low-density plasma [2][3][4][5] . The exception was the TMX-U experiment at Lawrence Livermore National Laboratory where electron temperatures up to 0.28 keV were obtained with ECR heating (ECRH), but these studies were terminated soon after that 6 .…”
Section: Introductionmentioning
confidence: 99%
“…This simplified view is widely spread over the fusion community. That in combination to many experiments which never demonstrated the electron temperature higher than 280 eV [6], led to a judgment that the very concept of a thermonuclear reactor based on a magnetic mirror has hit a dead end. This results in a relatively weak research activity in this field.…”
Section: Introductionmentioning
confidence: 99%
“…However, for many years the use of this method in open magnetic configurations has been limited either by plasma heating in relatively compact laboratory installations 1 , or by MHD stabilization of low-density plasma [2][3][4] . The only exception was the TMX-U experiment at Lawrence Livermore National Laboratory where electron temperatures up to 0.28 keV were obtained with ECR heating, but these studies were concluded soon 5 . And only recently an efficient ECR heating of a dense (comparable to toroidal devices) plasma has been demonstrated at a large-scale mirror trap.…”
Section: Introductionmentioning
confidence: 99%